1983
DOI: 10.1007/bf01324951
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on gastric emptying of liquid-solid meals in man

Abstract: A dual radioisotopic method was employed to study the rate of gastric emptying of meals in ten males with an average age of 31 years and 10 elderly males with an average age of 76.4 years. All study subjects were fed a standardized 900-g meal labeled with a liquid (111indium-DTPA) and solid (99mtechnetium-tagged liver) phase isotopic marker. There were no significant differences in solid food emptying rates between the young and aged men. A delay in liquid emptying, however, was observed in the aged men. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
1
5

Year Published

1985
1985
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(68 citation statements)
references
References 10 publications
3
59
1
5
Order By: Relevance
“…The power ratio was significantly lower in the elderly groups, indicating that the postprandial gastric contractile force is reduced (hypomotility), resulting in a delay of gastric emptying in the elderly [20]. This delayed gastric emptying time was also demonstrated by the simultaneously delayed 13 CO 2 expiration peak time in the elderly.…”
Section: Discussionmentioning
confidence: 71%
“…The power ratio was significantly lower in the elderly groups, indicating that the postprandial gastric contractile force is reduced (hypomotility), resulting in a delay of gastric emptying in the elderly [20]. This delayed gastric emptying time was also demonstrated by the simultaneously delayed 13 CO 2 expiration peak time in the elderly.…”
Section: Discussionmentioning
confidence: 71%
“…Dysmotility in the gastrointestinal tract increases with ageing [1][2][3][4][5][6]. Constipation and faecal incontinence are common symptoms in the elderly [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This finding adds further support to the notion that age is possibly one of the factors that drives dyspeptic symptoms in peptic ulcer disease. However, it has been shown that age does not have a major influence on gastric emptying [41,42,43], and patients with uPUD were similar in age to the controls, yet had significantly delayed gastric emptying. Thus, age differences in this study are unlikely to affect the results of gastric emptying studies.…”
Section: Discussionmentioning
confidence: 99%